Metabolomic profiling of antioxidant and anti-inflammatory properties in diatom Chaetoceros calcitrans extracts using NMR and UHPLC-MS coupled with chemometric analysis - Azizan, Awanis (2019)
Chaetoceros calcitrans is a diatom microalga that is known to be rich of amino acids, lipids, fatty acids and natural pigments identified as potentially important natural antioxidant and anti-inflammation. Nevertheless, little is known about the metabolome and the antioxidative and anti-inflammatory ability of the indigenous microalga, C. calcitrans. The main objectives of this study were to evaluate the metabolites that contributed to the antioxidant activity (DPPH*), nitric oxide (NO) inhibitory activity and total phenolic content (TPC) of C. calcitrans, extracted with different solvent polarities, including 70% ethanol, methanol, hexane, acetone, and chloroform using multi-platform metabolomics approaches. Nuclear magnetic resonance (NMR) coupled to multivariate data analysis (MVDA) was applied for the metabolomics profiling and relative quantification of the extracts. Further confirmation of the metabolites identification and quantitation were performed using ultra-high performance liquid chromatography mass spectrometry (UHPLC-MS). The results showed that acetone and chloroform (CHCl3) extracts of C. calcitrans revealed higher levels of TPC with 30.79 and 25.41 mg GAE/g dw, respectively. Both extracts also displayed moderate activity of DPPH radical scavenging inhibition with 43.01 and 35.03% at concentration 333 μg/ml. Furthermore, the CHCl3 extract inhibited the release of NO production from the LPS-activated RAW 264 cells with an IC50 value of 3.46 μg/ml. Twenty-nine metabolites were identified via NMR analyses from C. calcitrans extracts including 6 fatty acids, cholesterol, 11 amino acids, 2 sugars and 1 sugar-alcohol, 6 carotenoids and 2 chlorophylls. The structures of the compounds were also confirmed using tandem mass spectrometry. The main identified secondary metabolites were carotenoids including fucoxanthin, lutein, astaxanthin, canthaxanthin, zeaxanthin and violaxanthin. Comparison of different extracts revealed clear differences in the metabolite profiles and the partial least square (PLS) model indicated that the carotenoids were significantly associated with the tested bioactivities. The results suggested CHCl3 and acetone extracts of C. calcitrans showed the abundance of high-value metabolites as markers for antioxidant and anti inflammatory activities. The findings from this research may serve as a benchmark for future extraction processes particularly in recovering antioxidant and anti-inflammatory metabolites derived from diatom. These metabolites can be important active ingredients for medicinal preparation, functional foods, and cosmeceutical and nutraceutical applications.